1999
DOI: 10.1093/intqhc/11.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outpatient clinics: are we allowing enough time?

Abstract: The amount of time spent by patients with surgeons is already so short as to cause concern about both the appropriateness and value of consultations. It is unreasonable to increase workload further. There is a clear need for outpatient clinics to be managed, with regular examination of what is taking place and how long it takes. Only then will it be possible to tailor schedules to the actual requirements of the service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…10 In studies of general surgical outpatient clinics, it was found that 27% of patients thought the time spent with their doctor was too short and that 78% of clinics over-ran their schedule time. [11][12][13] A recent audit of 10 consecutive routine urology outpatient clinics showed that the mean time spent with the patient in 2001 was 4.8 minutes, which contrasts sharply with the figure of 7.6 minutes obtained during their departments' previous audit in 1988. 14 15 These data do not sit easily with evidence that shows that the length of time spent with the surgeon is of paramount importance to patients' overall satisfaction of the outpatient clinic process.…”
Section: Discussionmentioning
confidence: 94%
“…10 In studies of general surgical outpatient clinics, it was found that 27% of patients thought the time spent with their doctor was too short and that 78% of clinics over-ran their schedule time. [11][12][13] A recent audit of 10 consecutive routine urology outpatient clinics showed that the mean time spent with the patient in 2001 was 4.8 minutes, which contrasts sharply with the figure of 7.6 minutes obtained during their departments' previous audit in 1988. 14 15 These data do not sit easily with evidence that shows that the length of time spent with the surgeon is of paramount importance to patients' overall satisfaction of the outpatient clinic process.…”
Section: Discussionmentioning
confidence: 94%
“…These studies differ from the current service evaluation by reviewing aspects of care in absolute terms, and not comparatively, and therefore cannot be used to determine those steps within the pathway that patients prioritize and that reflect the greatest value in their healthcare journey. However, it is recognized that the nature of the process and environment involved in the patient pathway can also influence the quality of the consultation even if considered of low relative importance, for example by limiting patient-doctor interaction [37].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this leads to shorter consultation times. It has also been shown that satisfaction among patients and doctors declines rapidly when consultations last under 10 min 6 . Tristram Lesser in a letter to ENT News talks of the perils of seeing too many patients in one clinic session 7…”
Section: Discussionmentioning
confidence: 99%
“…However, the BAOL, in its consultation document, has suggested an average of 14 min per patient 5 . On the basis of other research, it has been argued that a reasonable duration for an appointment at a surgical out‐patient clinic is 20 min for a new appointment and 10 min for a follow‐up 6 …”
Section: Discussionmentioning
confidence: 99%